Dynamic reconstruction based representation learning for multivariable process monitoring. (September 2019) - Lv, Feiya; Wen, Chenglin; Liu, Meiqin
Highlights: A dynamic reconstruction based representation learning method for multivariable process monitoring is proposed in this paper. A multi-layered Tayler network is efficient to approximate smooth sigmoid functions. The dynamic reconstruction based on kNNs can not only maintain the separability of the original data, but also increase the distinguishable distance between categories. The representations formed by the composition of multiple non-linear transformations, are efficient for the detection of incipient faults. Abstract: Representation learning is a key step for fault detection in the process monitoring. With the consideration of time-correlated, this paper focus on developing a dynamic representation learning method yields high-order correlations in process monitoring. First, a general interpretation of AE net is presented based on Taylor expansion, which motivates the representation ability by the composition of multiple non-linear transformations. Due to the fact that the nearest neighbors over time are not necessarily the nearest spatial neighbors in dynamic process, a dynamic reconstruction is developed based on its k nearest neighbors. The reconstruction can not only maintain the separability, but also increase the distinguishable distance between categories. Finally, numerical results shown that a multi-layer Taylor network is efficiently to approximate the smooth sigmoid functions of AE net, and experiments on Tennessee Eastman process (TEP) illustrated the proposed method's superior detectability, specifically for incipient faults.